RANCANG BANGUN ALAT PEMBUAT MINUMAN OTOMATIS BERBASIS ARDUINO UNO - Sitorus, Halasan Pardamean; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2020)
The rapid development of automatic technology at this time penetrated all fields, especially in the field of food and beverages. One of them is an automatic beverage machine that can make drinks more practical in terms of mixing the ingredients of drinks, stirring and pouring water. In the automatic beverage machine there is still a weakness, namely the user is still in physical contact, pressing the menu and still having to go to the machine and wait for the process to finish. Based on these weaknesses, an automatic beverage maker is made by ordering drinks through an Android-based smartphone application connected to the beverage machine through ESP 8266 then processed arduino uno. The motor shield as a control in removing ingredients in the manufacture of drinks and relay module as control motor stirrer, motor pump, solenoid valve and buzzer. Percentage of error for each brewing ratio is bitter coffee with a percentageof an error 4,26 %, sweet coffee with a percentage of an error 3,60 %, milk drinks with an error percentage of 3,60 % and milk coffee with an error percentage of 3,92 %.